Ixekizumab successfully treated severe pityriasis rubra pilaris after COVID‐19 vaccination - Ya‐ting Liu; Shang‐shang Wang (Wiley, 2023)
Abstract Pityriasis rubra pilaris is an inflammatory dermatologic disorder of unknown cause. We report a 67‐year‐old man with Pityriasis rubra pilaris might induced by COVID‐19 vaccination. The patient developed the lesions after the first dose of vaccine and significantly aggravated after the second dose. He had poor effect and liver function impairment developed after acitretin used, but achieved satisfactory efficacy after replacement to ixekizumab, an interleukin‐17A inhibitor.